2011
DOI: 10.1080/1351847x.2010.538300
|View full text |Cite
|
Sign up to set email alerts
|

Are there any cost and profit efficiency gains in financial conglomeration? Evidence from the accession countries

Abstract: Diversified banks should benefit from an efficient allocation of resources, debt coinsurance and scope economies. At the same time, critics of diversification question these advantages pointing to agency problems such as managerial entrenchment and empire building that could also lead to diversification but for the 'wrong' reasons. This paper sheds further light on the issue of bank diversification by taking a direct look into how efficiently financial conglomerates operate and by measuring to what extent size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 40 publications
2
18
0
1
Order By: Relevance
“…Our results indicate that lower risk is related to a higher survival time for cooperative banks. These findings contribute to the existing literature that investigates the direct link between efficiency and risk-taking (Chortareas et al, 2011;Chronopoulos et al, 2011;Fiordelisi et al, 2011) by showing that prudent and skilful managerial abilities increase the survival time of cooperative banks. To support our view, we test three research hypotheses that focus on the contribution of efficiency to the probability of bank failure.…”
Section: Discussionsupporting
confidence: 62%
“…Our results indicate that lower risk is related to a higher survival time for cooperative banks. These findings contribute to the existing literature that investigates the direct link between efficiency and risk-taking (Chortareas et al, 2011;Chronopoulos et al, 2011;Fiordelisi et al, 2011) by showing that prudent and skilful managerial abilities increase the survival time of cooperative banks. To support our view, we test three research hypotheses that focus on the contribution of efficiency to the probability of bank failure.…”
Section: Discussionsupporting
confidence: 62%
“…The current studies in the world on the effect of income diversification on the performance of commercial banks also led to different conclusions that income diversification played an important role in bank efficiency. The research by Chronopoulos et al (2011), Lee et al (2014) supported the view point that income diversification would help banks increase efficiency. Whereas the studies of Vennet (2002), Stiroh and Rumble (2006), Elyasiani and Wang (2012) and a series of other studies indicated that income diversification or bank activities had an inverse relationship with operational efficiency and even increased risks for banks.…”
Section: Introductionmentioning
confidence: 66%
“…Klein and Saidenberg (1997) argued that the combination of banking services would generate stable income, optimize management costs and contribute to bank profits; banks with non-interest trading reduce the volatility of profits (Santomero & Chung, 1992). Chronopoulos et al (2011) used data envelopment analysis (DEA) to estimate both cost and profitability of banks in the early stages. The results show that there was a high efficiency of both the costs and profitability of banking operations.…”
Section: Literature Reviewmentioning
confidence: 99%